Lay perspectives on causes and complications of hypertension; and barrier to access health care by known hypertensive patients: a qualitative study from a rural area of South India - Newtonraj, Ariarathinam; Arun, Sugumaran; Bazroy, Joy; Tovia, Stephen (International Journal Of Community Medicine And Public Health, 2017)
Background: Global prevalence of hypertension in the year 2000 was estimated to be 26% with approximately 1 billion people affected by it. By 2025 this has been projected to increase to 29% increase to 29%, expecting greater proportion of population will be consists of elderly people. Limited qualitative studies on hypertension are available in India. We intended to conduct a qualitative study on the perception about hypertension causes, complications and barrier to get medications, among known hypertensive patients residing in rural area or south India. Methods: A qualitative study has been undertaken in August 2016 by the interns posted in Rural Health Training Centre of Pondicherry Institute of Medical Sciences (RHTC-PIMS). The study was completed after conducting in depth interview among 40 randomly selected known hypertensive patients. All the interviews were audio taped. Verbatim were done from the recording in local language (Tamil) and then translated to English. Coding and thematic analysis was done by analysis team consisting of one Assistant Professor in Community Medicine, one medical social worker (MSW) and three interns. Results: There is a huge lack of awareness about the causes of hypertension among the patients. There is also a huge lack of awareness about the complications of hypertension, among hypertensive patients. This may result in poor adherence to medication and prevention of complications. Almost all the patients reported that they were following Allopathic medications and getting medications from government primary health centre. There is a need to visit the health centre every week, as the medicines provided to them are only weekly basis. Conclusions: There is a huge lack of knowledge about hypertension among known hypertensive patients. There is a need for a holistic approach in managing hypertensive patients in rural area in India.